Analysis of cooperative accountability in Kediri regency in a Javanese perspective: Memayu Hayuning Bawono Dur Angkoro - Bella Paradita; Eko Prasetyo; Qurnainin Qutbatun Nisa (Institute of Computer Science (IOCS), 2023)
The Savings and Loan Cooperative is a business entity based on kinship. Management of Savings and Loans Cooperatives requires Good Corporate Governance which affects cooperative accountability. Accountability of Savings and Loans Cooperatives in savings and loan cooperatives is not optimal due to limited human resources. Formation resource depends on environmental culture, Belief in God, Self. Memayu Culture Hayuning Bawono Dur Angkoro. One of them that influences human behavior This study aims to interpret the Javanese philosophy of Memayu Hayunng Bawono Dur Angkoro, namely about God, ourselves and the environment. To Accountability of Savings and Loans Cooperatives in Kediri Regency. The synergy of Memayu Hayuning Bawono is that it has values (1) Tatas, Tutus, Titis, Titi Lan Wibawa, and no ranglasakake gatra,(2) Thorough and careful (3) Behavior karyenaktyasing Sesama (4) Mindful and vigilant behaviour. This research uses qualitative methods with ethnography approach using interviews. The results of the study are that the Kediri Savings and Loans Cooperative does not yet have good accountability due to limited knowledge, but the savings and loan cooperatives have implemented financial reports properly. Savings and loan cooperatives in acting are guided by culture, namely MHB, which is reflected in their relationship with customers, namely mutual respect.